How does institutional support affect the coalbed methane industry? - Wei, Jie; Niu, Chong-Huai (Frontiers in Energy Research, 2023)
Accelerating the construction of a low-carbon, safe, and modern energy system is becoming a critical developmental path toward solving the climate change problem. China provides institutional support in various ways for this clean and efficient new energy, but there is still a gap between the developmental scale and the planned target. Considering the theory of system support and the coalbed methane industry, we combed the existing institutional support for the coalbed methane industry based on grounded theory and defined the initial model. We used the system dynamics method to construct and simulate the model and verified the system’s effectiveness by using the goodness of fit. The results show that institutional support promotes the development of the coalbed methane industry, and the interaction between the two forms a dynamic system. Based on the sensitivity analysis method, the enlightenment of the management with respect to the improvement of the development of the coalbed methane industry was obtained. Firstly, the management of coalbed methane mining rights should be supervised and large-scale utilization should be strengthened. Secondly, the central government’s subsidies should be raised and local governments should be encouraged to provide support. Thirdly, technological innovation should be enhanced and fair competition should be ensured.